Localized scleroderma (morphea). Diagnostic and therapeutic recommendations of the Polish Dermatological Society - Dorota Krasowska; Lidia Rudnicka; Aleksandra Dańczak-Pazdrowska; Grażyna Chodorowska; Anna Woźniacka; Anna Lis-Święty; Joanna Czuwara; Joanna Maj; Sławomir Majewski; Anna Sysa-Jędrzejowska; Anna Wojas-Pelc (Termedia Publishing House, 2019)
Localized scleroderma (morphea) is a chronic autoimmune disease of the connective tissue. Its etiopathogenesis is unknown. Most often the disease affects the skin, but may also involve the subcutis, muscles, and the osteoarticular system. The clinical presentation and the course of disease may be diverse. This article presents clinical characteristics of various types of the disease, the classification of its subtypes, recommendations for differential diagnosis and treatment.